2011
DOI: 10.2166/ws.2011.066
|View full text |Cite
|
Sign up to set email alerts
|

Reliability assessment of water distribution systems with statistical entropy and other surrogate measures

Abstract: There is ever increasing commercial and regulatory pressure to minimise the cost of water distribution networks even as the demand for them keeps on growing. But cost minimizing is only one of the demands placed on the network design. Satisfactory networks are required to operate above a minimum level even if they experience failure of components. Reliable hydraulic performance can be achieved if sufficient redundancy is built in the network. This has given rise to various water distribution system optimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 21 publications
2
23
2
Order By: Relevance
“…Farmani et al (2005Farmani et al ( , 2006 considered the resilience index (Todini 2000) and water age (Rossman 2002). Prasad and Tanyimboh (2008) investigated the statistical flow entropy (Tanyimboh and Templeman 2000;Tanyimboh et al 2011) and resilience index. More recently Atkinson et al (2014) maximized flow entropy and resilience index at once in an attempt to generate hybrid solutions with properties derived from the two measures.…”
Section: Introductionmentioning
confidence: 99%
“…Farmani et al (2005Farmani et al ( , 2006 considered the resilience index (Todini 2000) and water age (Rossman 2002). Prasad and Tanyimboh (2008) investigated the statistical flow entropy (Tanyimboh and Templeman 2000;Tanyimboh et al 2011) and resilience index. More recently Atkinson et al (2014) maximized flow entropy and resilience index at once in an attempt to generate hybrid solutions with properties derived from the two measures.…”
Section: Introductionmentioning
confidence: 99%
“…Initially Tanyimboh and Sheahan (2002) and Tanyimboh and Setiadi (2008) generated the designs to investigate flow entropy. Subsequently Tanyimboh et al (2011) used the designs to investigate resilience index. The head at the supply node is 100 m; demand node elevations are 0 m; required residual head at demand nodes is 30 m; pipes are 1000 m long; Hazen-Williams roughness coefficient is 130; pipe diameters are continuous in the range 100 to 600 mm.…”
Section: Examplementioning
confidence: 99%
“…The available evidence suggests that higher entropy values increase the uniformity of the pipe diameters along with the reliability (Tanyimboh and Templeman 1993b;Tanyimboh and Setiadi 2008). Strong positive correlation between flow entropy and both hydraulic reliability and failure tolerance has been reported (Tanyimboh and Templeman 2000;Tanyimboh et al 2011;Gheisi and Naser 2015). Atkinson et al (2014) observed that an increase in entropy promotes an increase in capacity that is more globally distributed throughout the distribution network.…”
mentioning
confidence: 94%
See 2 more Smart Citations